2016
DOI: 10.1111/liv.13341
|View full text |Cite
|
Sign up to set email alerts
|

Wisteria floribunda agglutinin‐positive human Mac‐2 binding protein predicts the risk of HBV‐related liver cancer development

Abstract: WFA -M2BP level can independently predict HCC development. Further studies should investigate whether WFA -M2BP level could be incorporated into surveillance strategies for CHB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…The effect of underlying liver disease on M2BPGi performance should also be evaluated in greater depth. M2BPGi has been shown to be predictive of HCC in East Asian cohorts with HCV, HBV, and NAFLD but with different optimal threshold values in each . We found that there was a significant interaction between underlying liver disease and M2BPGi in our cohort, even after taking cirrhosis into account.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The effect of underlying liver disease on M2BPGi performance should also be evaluated in greater depth. M2BPGi has been shown to be predictive of HCC in East Asian cohorts with HCV, HBV, and NAFLD but with different optimal threshold values in each . We found that there was a significant interaction between underlying liver disease and M2BPGi in our cohort, even after taking cirrhosis into account.…”
Section: Discussionmentioning
confidence: 58%
“…It is possible that alternative lectins could improve the test’s performance in non‐Japanese HCV populations. For HBV, M2BPGi has been successfully used in Korean and Chinese populations in addition to Japanese populations, demonstrating that the test is robust to some changes in patient population …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, glycan analysis of M2BPGi in patients with chronic hepatitis C should be performed similarly to that for AFP‐L3 . In addition to their utility as markers of fibrosis, serum levels of M2BPGi were found to be useful for the prediction of HCC development . Similar phenomena have been observed for other glyco‐biomarkers, such as fucosylated haptoglobin, suggesting that aberrant glycan alteration occurs in the early stages of hepatocarcinogenesis, and that such alterations might be useful biomarkers for diagnosis.…”
Section: Glyco‐biomarkers For Liver Diseasesmentioning
confidence: 71%
“…In the recent years, M2BPGi has emerged as a novel biomarker that correlates well with hepatic fibrosis in patients with chronic liver diseases . Recent literature also suggests that M2BPGi may correlate with hepatocellular carcinoma (HCC) development in patients with chronic viral hepatitis, but most have been conducted in patients with chronic hepatitis C (CHC) or untreated chronic hepatitis B (CHB) without serial measurements …”
Section: Introductionmentioning
confidence: 99%